Revealing microstructure and dislocation behavior in BAlN/AlGaN heterostructures. (18th December 2017) - Sun, Haiding; Wu, Feng; Park, Young Jae; Al tahtamouni, T. M.; Liao, Che-Hao; Guo, Wenzhe; Alfaraj, Nasir; Li, Kuang-Hui; Anjum, Dalaver H.; Detchprohm, Theeradetch; Dupuis, Russell D.; Li, Xiaohang
Abstract: We reveal the microstructure and dislocation behavior in 20-pair B0.14 Al0.86 N/Al0.70 Ga0.30 N multiple-stack heterostructures (MSHs) exhibiting an increasing dislocation density along the c -axis, which is attributed to the continuous generation of dislocations (edge and mixed-type) within the individual B0.14 Al0.86 N layers. At the MSH interfaces, the threading dislocations were accompanied by a string of V-shape pits extending to the surface, leading to interface roughening and the formation of surface columnar features. Strain maps indicated an approximately 1.5% tensile strain and 1% compressive strain in the B0.14 Al0.86 N and Al0.70 Ga0.30 N layers, respectively. Twin structures were observed, and the MSH eventually changed from monocrystalline to polycrystalline.